Does Banking Market Structure Matter to Growth? Evidence from Ecuador - Loayza, Viviana del Cisne Espinoza (Journal of Ecohumanism, 2024)
This paper aims to determine how the banking market structure affects growth in Ecuador at a country and regional level. Banking concentration is significant for the country’s economic growth, although it has no effect in regions that are intensive in primary production and has a positive impact in areas where the commercial sector predominates. The Granger-Sims test shows that banking concentration negatively affects the country´s economic growth in the long run. We also found that credit deepening positively affects growth in regions with robust financial systems, while adverse effects are in areas with less financial development.